Immune Checkpoint Molecules—Inherited Variations as Markers for Cancer Risk - Wagner, Marta; Jasek, Monika; Karabon, Lidia (Frontiers in Immunology, 2021)
In recent years, immunotherapy has been revolutionized by a new approach that works by blocking receptors called immune checkpoints (IC). These molecules play a key role in maintaining immune homeostasis, mainly by suppressing the immune response and by preventing its overactivation. Since inhibition of the immune response by IC can be used by cancer to avoid recognition and destruction by immune system, blocking them enhances the anti-tumor response. This therapeutic approach has brought spectacular clinical effects. The ICs present heterogeneous expression patterns on immune cells, which may affect effectiveness of immunotherapy. The inherited genetic variants in regulatory regions of ICs genes can be considered as one of factors responsible for observed inter-individual differences in ICs expression levels on immune cells. Additionally, polymorphism located in exons may introduce changes to ICs amino acid sequences with potential impact on functional properties of these molecules. Since genetic variants may affect both expression and structure of ICs, they are considered as risk factors of cancer development. In this review, we have comprehensively summarized the current understanding of the relationship between inherited variations in genes encoding ICs and cancer risk. From numerous studies it can be concluded that polymorphisms within CTLA-4 (CTLA-4 c.49A> G; CTLA-4g.319C>T; CT60; CTLA-4g.1661A>G), PDCD1 (PD1.1C>T; PD-1.5C>T; PD-1.9C>T) and PD-L1 (rs4143815G>C) are associated with overall cancer risk, as well as with the risk of developing certain types of cancer. We have also conducted a review of published reports concerning genetic variants of BTLA, TIM3, LAG3, and TIGIT. This analysis revealed that the BTLA and TIM3 gene variations (rs1982809, rs9288953, rs1844089, rs2705535 and -1516G>T, -822C>T, -574G>T, +4259T>G, respectively) may be considered as risk factors of cancer. The main conclusion which can be drawn from our review is that variants in genes encoding ICs might be considered as low-risk variants for cancer development, which has been well documented by numerous reports for CTLA-4, PDCD1, PD-L1 genes, whereas for BTLA, TIM3, LAG3, and TIGIT more studies investigating association between genetic variants of these genes and various types of cancer have to be conducted before any definitive conclusion can be reached.